A Combination of Gestalt Therapy, Rosen Body Work, and Cranio Sacral Therapy did not help in Chronic Whiplash-Associated Disorders (WAD) - Results of a Randomized Clinical Trial. (2004) - Ventegodt, Søren; Merrick, Joav; Andersen, Niels J.; Bendix, Tom
Abstract : The chronic state of whiplash-associated disorder (WAD) might be understood as a somatization of existential pain. Intervention aimed to improve quality of life (QOL) seemed to be a solution for such situations. The basic idea behind the intervention was holistic, restoring quality of life and relationship with self, in order to diminish tension in the locomotion system, especially the neck. A psychosomatic theory for WAD is proposed. Our treatment was a short 2-day course with teachings in philosophy of life, followed by 6 to 10 individual sessions in gestalt psychotherapy and body therapy (Rosen therapy and Cranio Sacral therapy), followed by a 1-day course approximately 2 months later, closing the intervention. Two independent institutions did the intervention and the assessments. In a randomized, clinically controlled setting, 87 chronic WAD patients were included with a median duration of 37 months from their whiplash accidents. One patient never started. Forty-three had the above intervention (female/male = 36/7, ages 2249, median 37 years) and another 43 were assigned to a nontreated control group (female/male = 35/8, ages 1848, median 38). Six had disability pension and 27 had pending medicolegal issues in each group. Effect variables were pain in neck, arm, and/or head; measures of quality of life and daily activities; as well as general physical or mental health. Wilcoxon test for between-groups comparisons with intention-to-treat analyses was conducted; the square curve paradigm testing for immediate improvements of health and quality of life was also used. The groups were comparable at baseline. From the intervention group, 11 dropped out during the intervention (4 of those later joined the follow-up investigation), 22 of the remaining 32 graduated the course, and 35 of the 43 controls did as well. Approximately 3 months later, we found no clinically relevant or significant increase in any effect measure. The above version of a quality of life intervention based on alternative therapy had no effect on patients with chronic WAD.